High precision astrometry with adaptive optics aided imaging - Meyer, Eva (2010)
Currently more than 450 exoplanets are known and this number increases nearly every day. Only a few constraints on their orbital parameters and physical characteristics can be determined, as most exoplanets are detected indirectly and one should therefore refer to them as exoplanet candidates. Measuring the astrometric signal of a planet or low mass companion by means of measuring the wobble of the host star yields the full set of orbital parameters. With this information the true masses of the planet candidates can be determined, making it possible to establish the candidates as real exoplanets, brown dwarfs or low mass stars. In the context of this thesis, an M-dwarf star with a brown dwarf candidate companion, discovered by radial velocity measurements, was observed within an astrometric monitoring program to detect the astrometric signal. Ground based adaptive optics aided imaging with the ESO/NACO instrument was used with the aim to establish its true nature (brown dwarf vs. star) and to investigate the prospects of this technique for exoplanet detection. The astrometric corrections necessary to perform high precision astrometry are described and their contribution to the overall precision is investigated. Due to large uncertainties in the pixel-scale and the orientation of the detector, no detection of the astrometric orbit signal was possible ...
Keywords: Hochschulschrift; Astronomie; Max-Planck-Institut für Astronomie